Fimbriae‐mediated outer membrane vesicle production and invasion of Porphyromonas gingivalis. Issue 1 (18th December 2014) - Mantri, Chinmay K.; Chen, Chin‐Ho; Dong, Xinhong; Goodwin, Jeffery Shawn; Pratap, Siddharth; Paromov, Victor; Xie, Hua
Abstract Porphyromonas gingivalis is a keystone periopathogen that plays an essential role in the progress of periodontitis. Like other gram‐negative bacteria, the ability of P. gingivalis to produce outer membrane vesicles is a strategy used to interact with, and survive within its biological niches. Here we compared the protein components associated with vesicles derived from a fimbriated strain (33277) and an afimbriated strain (W83) of P. gingivalis using proteomic analyses. Some well‐known virulence factors were identified in vesicles from both strains, such as gingipains and hemagglutinin. In contrast, FimC, FimD, and FimE, minor components of long fimbriae were found exclusively in 33277 vesicles, while proteins with a tetratricopeptide repeat (TPR) domain were unique to W83 vesicles. We found that significantly more 33277 than W83 vesicles were internalized into human oral keratinocytes and gingival fibroblasts. Interestingly, FimA, a well‐known adhesin responsible for the attachment and invasion of P. gingivalis into host cells, was not essential for the invasive capabilities of P. gingivalis vesicles. Rather minor components of long fimbriae were required for an efficient invasive activity of vesicles. The most striking finding was that P. gingivalis strains lacking or having a reduced FimA expression showed a significant reduction in vesiculation. These results suggest that production and pathogenicity of P. gingivalis vesicles may largely depend on expression of the fim locus, and that the integration of vesicle production and pathogenicity with fimbrial expression may allow P. gingivalis to confer upon itself certain functional advantages.